Analisis Faktor-Faktor Yang Mempengaruhi Terhadap Keputusan Penggunaan Shopee Paylatter Di Provinsi Bengkulu - Hennie Vianora; Effed Darta Hadi; Muhammad Rusdi (Student Journal of Business and Management, 2023)
This research aims to determine whether there is an influence of Paylater payments on the desire to use Shopee Paylatter in Bengkulu province. This research uses five variables, namely one dependent variable (Y) and four independent variables (X). variable Y is intention to use, variable X1 is convenience, variable X2 is benefit, variable X3 is risk and variable X4 is trust. Data collection was carried out using a questionnaire to 169 respondents. To see the influence of the independent variable on the dependent variable, the analysis was carried out using multiple linear regression analysis. The results of the research state that variable X1 (comfort) has a coefficient of 0.374, variable X2 (comfort) has a coefficient of 0.628 and variable ) has a coefficient of -0.493. The three variables that give positive values indicate that the comfort, benefit and trust variables have a positive influence on the desire to use the Shopee Paylatter application. On the other hand, variable X3 (risk) can have a negative influence on consumers' desire to use the Shopee Paylatter application. The independent variables, namely variables X1 (comfort), X2 (benefits), and X4 (trust) in this study show a significant influence on variable Y (intention to use). With a value for each variable of 0.000 (> alpha 0.05), and variable X4 (trust) which has an insignificant effect is 0.455